(untitled) (Journal of history, 2024)
After the destruction of the Dzungars, the Kazakh Khanate and the Qing Dynasty established official political and economic relations. This year is always called “the year of the cow” in Kazakh documents, it corresponds to 1757 according to the Gregorian calendar. After that, trade between the two sides began to flourish, at first cattle were traded in Urumqi (1758), then trade fairs were opened one after another in Yili (1761) and Tarbaghatai (1764). Such types of trade developed rather quickly in the eastern border regions of Kazakhstan, which were mostly owned by Abylai, Abilpeyiz and their descendants. Due to the expansion of the relationship between the two sides, the number of correspondence has also increased. According to the results of the author’s research in the First Historical Archive of China, there are more than 150 Kazakh documents, most of which are letters written by Kazakh khans and sultans. Among these, we can find the letters written by Sultan Bopy to the Qing Dynasty. Bopy Sultan descends from Abilpeyiz, the 2nd son of Abilmambet, the great Kazakh khan. He was one of the most influential sultans in his time. The letters on which our article is based are the letters sent by this Bopy Sultan to the Qing prince who was in charge of affairs in Tarbaghatai in 1789. The language of these letters is simple, the content is understandable, they are a very valuable historical source in the study of social history, culture and ancient language and writing of the Kazakh Khanate of the 18th century.